2019
DOI: 10.1136/oemed-2018-105592
|View full text |Cite
|
Sign up to set email alerts
|

Night work and miscarriage: a Danish nationwide register-based cohort study

Abstract: ObjectiveObservational studies indicate an association between working nights and miscarriage, but inaccurate exposure assessment precludes causal inference. Using payroll data with exact and prospective measurement of night work, the objective was to investigate whether working night shifts during pregnancy increases the risk of miscarriage.MethodsA cohort of 22 744 pregnant women was identified by linking the Danish Working Hour Database (DWHD), which holds payroll data on all Danish public hospital employee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 34 publications
0
57
1
11
Order By: Relevance
“…A recent report suggested that night work was not associated with an elevated risk of preterm birth. 11 In contrast, Begtrup et al 12 suggested that night workers might have an increased risk of miscarriage compared with the risk in pregnant women not working night shifts. The result in the present study was concordant with that of the former report despite the increased risks of threatened miscarriage and threatened preterm labor, which might be a result of obstetricians prescribing complete rest for most pregnant women facing threatened miscarriage or threatened preterm labor with signs of genital bleeding.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…A recent report suggested that night work was not associated with an elevated risk of preterm birth. 11 In contrast, Begtrup et al 12 suggested that night workers might have an increased risk of miscarriage compared with the risk in pregnant women not working night shifts. The result in the present study was concordant with that of the former report despite the increased risks of threatened miscarriage and threatened preterm labor, which might be a result of obstetricians prescribing complete rest for most pregnant women facing threatened miscarriage or threatened preterm labor with signs of genital bleeding.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the majority of pregnant women were recruited after the latter half of the first trimester, which means that early miscarriages were not covered in the JECS. Thus, we did not analyze the risk of early miscarriages despite its importance as an occupational health issue …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations